Social Support in Determining Coping Strategies Among Adolescents in Urban City: Evidence from Post COVID-19 - Rizkiyani Istifada; Firda Widyasari; Hera Hastuti; Robby Prihadi Aulia Erlando (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: The process of life has changed in the post-pandemic COVID-19 era, including in the educational setting of schools. This condition has an impact on adolescents who tend to struggle in determining effective coping strategies. Adolescents require a lot of support in resolving their chosen coping strategies. Objectives: This research aims to explain the relationship between social support and coping strategies among adolescents in the post-pandemic COVID-19 era. Methods: This research used a quantitative approach with a cross-sectional design. The research sample consists of 11th-grade students attending schools in the urban city, with 224 respondents. The sampling technique used in this study is random sampling. The correlation between social support and coping strategies is analyzed using the Chi-square test with normally distributed data. Results: This research indicates a relationship between social support and coping strategies adolescents use during the learning process in Tangerang (p-value < 0.05). Conclusions: Adolescents with low social support tend to use problem-focused coping strategies, while the majority of adolescents with high social support tend to use emotion-focused coping strategies. This study recommends interventions for adolescent groups to determine appropriate coping strategies when experiencing stress.